Pediatric dental treatment: manifestations of stress in patients, mothers and dental school students Tratamento odontopediátrico: manifestações de estresse em pacientes, mães e alunos de Odontologia - Cármen Lúcia Cardoso; Sônia Regina Loureiro; Paulo Nelson-Filho (Sociedade Brasileira de Pesquisa Odontológica, 2004)
The aim of this study was to compare a group of children with high levels of anxiety during dental treatment who required physical restraint (group 1) to a group of children who collaborated with treatment (group 2). Child stress and its relationship with the manifestations of stress of the mothers and the dental students were assessed. The following psychological evaluation techniques were applied: the Child Stress Scale, the Rutter Parent Scale A2, Dental Fear Survey, and Lipp Stress Symptoms Inventory for Adults. Group 1 presented higher stress indicators, and emotional and behavior difficulties than group 2 (p < 0.01). The stress indicators and the dental fear presented by mothers from group 1 were higher than that from group 2 (p < 0.01). The dental students who treated the children from both groups presented high stress levels. We conclude that the difficulties experienced by the child and the mother, associated to the student's diminished ability to control the situation, may negatively influence the perception that the child has of dental treatment. A set of factors related to the children, mothers or dental students may cause poor collaboration during the dental treatment. O objetivo deste estudo foi comparar um grupo de crianças com altos níveis de ansiedade frente ao tratamento odontopediátrico que necessitaram de contenção física (grupo 1) a um grupo de crianças que colaboraram com o atendimento (grupo 2). Para tal, o estresse infantil e suas relações com manifestações de estresse de acompanhantes/mães e dos alunos de odontologia foram avaliados. Procedeu-se à aplicação das técnicas: Escala de Estresse Infantil, Escala Comportamental Infantil A2 de Rutter, "Dental Fear Survey" e Inventário de Sintomas de Estresse para Adultos de Lipp. O grupo 1 apresentou indicadores mais elevados de estresse e de dificuldades emocionais e comportamentais que o grupo 2 (p < 0,01). Os indicadores de estresse e de medo odontológico apresentados pelas mães do grupo 1 foram maiores que os apresentados pelas mães do grupo 2 (p < 0,01). Os alunos que atenderam as crianças dos dois grupos apresentaram elevados níveis de estresse. Conclui-se que as dificuldades vivenciadas pela criança e pelo acompanhante associadas à pouca capacidade do aluno para controlar a situação podem estar influenciando a percepção que a criança tem do tratamento odontológico. Um conjunto de fatores ligados às crianças, aos acompanhantes e aos alunos interferem nas manifestações de comportamentos pouco colaboradores no tratamento odontológico.